Blockchain-Based Management of Video Surveillance Systems - Jeong, Yena; Hwang, Dongyeop; Kim, Ki Hyung (International Conference on Information Networking, 2019)
In this paper, we propose a video surveillance system based on blockchain system. The proposed system consists of a blockchain network with trusted internal managers. The metadata of the video is recorded on the distributed ledger of the blockchain, thereby blocking the possibility of forgery of the data. The proposed architecture encrypts and stores the video, creates a license within the blockchain, and exports the video. Since the decryption key for the video is managed by the private DB of the blockchain, it is not leaked by the internal manager unauthorizedly. In addition, the internal administrator can manage and export videos safely by exporting the license generated in the blockchain to the DRM-Applied video player.
Keywords: IPFS; Proposed architectures; Video players; Video surveillance systems; Blockchain; Hyperledger Fabric; IPFS; Video Surveillance System